The Impact of Pancasila Values For Digital Economy in Small Enterprises - Meiriza, Mica Siar; Nura, Alfi; Sihaloho, Rebecca Putri; Simarmata, Rojelita Catrina; Nuraina, Azra Lena; Warasati, Rina Kartika; Sembiring, Olivia (CV. Rayyan Dwi Bharata, 2025)
This study examines how Pancasila values are implemented in digital businesses, particularly small enterprises, in Pasar Raya MMTC. The research aims to understand how Pancasila principles such as social justice, unity, and moral values are applied in the digital economy. A survey was conducted with 80 customers at Pasar Raya MMTC to assess their perceptions of small business practices aligning with Pancasila. The results indicate that small business owners who demonstrate moral principles, consider customer interests, and promote equitable offerings and treatment positively influence customer comfort and trust in digital transactions. The findings suggest Pancasila provides a valuable framework for ethical digital business practices that can support the growth and inclusion of small enterprises.